Barriers and facilitators influencing self-management among COPD patients: a mixed methods exploration in primary and affiliated specialist care - Hillebregt, Chantal F (Int J Chron Obstruct Pulmon Dis, 2016)
Self-management is becoming increasingly important in COPD health care although it remains difficult to embed self-management into routine clinical care. The implementation of self-management is understood as a complex interaction at the level of patient, health care provider (HCP), and health system. Nonetheless there is still a poor understanding of the barriers and effective facilitators. Comprehension of these determinants can have significant implications in optimizing self-management implementation and give further directions for the development of self-management interventions. Data were collected among COPD patients (N=46) and their HCPs (N=11) in three general practices and their collaborating affiliated hospitals. Mixed methods exploration of the data was conducted and collected by interviews, video-recorded consultations (N=50), and questionnaires on consultation skills. Influencing determinants were monitored by 1) interaction and communication between the patient and HCP, 2) visible and invisible competencies of both the patient and the HCP, and 3) degree of embedding self-management into the health care system. Video observations showed little emphasis on effective behavioral change and follow-up of given lifestyle advice during consultation. A strong presence of COPD assessment and monitoring negatively affects the patient-centered communication. Both patients and HCPs experience difficulties in defining personalized goals. The satisfaction of both patients and HCPs concerning patient centeredness during consultation was measured by the patient feedback questionnaire on consultation skills. The patients scored high (84.3% maximum score) and differed from the HCPs (26.5% maximum score). Although the patient-centered approach accentuating self-management is one of the dominant paradigms in modern medicine, our observations show several influencing determinants causing difficulties in daily practice implementation. This research is a first step unravelling the determinants of self-management leading to a better understanding.